Economic liberalization and productivity growth: Further evidence from Bangladesh - Salim, Ruhul (Routledge, 2003)
The impact of economic liberalization reforms on the productive performances ofmanufacturing firms remains a contentious issue in the literature. This paper attempts tocontribute to the debate by empirically estimating productivity growth of Bangladesh foodmanufacturing using firm level data before and after reform. Empirical results show that the share of output growth was accounted for by input growth in most sectors of this industry. In some sectors, the estimated rate of total factor productivity (TFP) growth is negligible or even negative. Decomposition of the TFP growth shows that technological progress plays a significant role in TFP growth across firms within the sub-sectors of this industry. Empirical results also show that the relative contribution of capacity realization to TFP growth is not substantial in inhibiting the industry?s high and sustained growth. These dismal performances indicate that the industries responded a little to the implementation of economic reforms.